Compressive behaviour of brick masonry triplets in wet and dry conditions. (1st May 2015) - Franzoni, Elisa; Gentilini, Cristina; Graziani, Gabriela; Bandini, Simone
Highlights: Samples of brick, cement mortar and natural hydraulic lime mortar were manufactured. Their compressive behaviour in dry and saturated conditions was investigated. Masonry triplets (cement mortar) were tested in dry, moist and saturated conditions. The results were correlated with the differences between materials microstructure. Abstract: Mechanical behaviour of old masonry may differ from the theoretical one to a great extent, hence it needs to be properly evaluated for quantifying the safety and serviceability of real structures, in view of their rehabilitation and/or seismic reliability assessment. Among the factors affecting such behaviour, the presence of moisture, mainly from rising damp, plays a key role in the deterioration state of old masonry structures, owing to salt crystallisation, frost damage, etc. Besides, water presence in the material pores may also directly influence their mechanical properties (compressive and tensile strength, elastic modulus), due to the interactions with the pore surface, enhancement of crack propagation velocity and other mechanisms. Although the effect of water saturation has been investigated for clay-bearing rocks, ceramics and concrete, its consequences on the mechanical behaviour of brick masonry still requires in-depth elucidation. For this reason, in the present paper the compressive strength and Young's modulus of fired-clay bricks, cement-based and lime-based mortars as well as masonry triplets are investigated, in dry and wet conditions. The results are interpreted in the light of the microstructural features of the materials, i.e., total voids amount and pores size distribution.